Exploring Effect of CACC Vehicle Types on Freeway Traffic Flow: Case Study on a Bosphorus Strait - Göncü, Sadullah; Silgu, Mehmet Ali; Akova, Hazal; Çelikoğlu, Hilmi Berk (Elsevier, 2025)
This study investigated the impact of integrating CACC-equipped buses into a mixed-autonomy environment within a singledirection bus rapid transit corridor. Utilizing a SUMO microsimulation of Istanbul’s Metrobus System, specifically the segment where BRT vehicles merge with regular traffic on the D-100 freeway to cross the 15 Temmuz Bridge in the Europe to Asia direction, we examined the effects of varying market penetration rates (MPRs) of CACC vehicles on throughput, total system travel time, emissions, and average speed on the bridge. Results revealed that increasing the MPR of CACC vehicles led to improved throughput, particularly when BRT buses were also CACC-equipped. This improvement came with a slight increase in total system travel time, but overall traffic efficiency was enhanced. Notably, CACC-equipped BRT buses caused minor disruptions in a fully human-driven traffic stream, highlighting the importance of consistent CACC implementation across vehicle types. While emissions generally increased with higher MPRs of CACC vehicles, the relative increase between scenarios with and without CACC-equipped buses remained minimal, suggesting a potential for environmental benefits alongside improved efficiency.
Keywords: CACC; Traffic Flow; Public Transportation; Microsimulation; Mixed Traffic